PERLINDUNGAN HUKUM TERHADAP ISTRI DALAM PERALIHAN HARTA BERSAMA TANPA PERSETUJUAN - Rohaningsih, Rohaningsih (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. Community property is all the assets acquired during the marriage, which by law becomes jointly owned by the husband and wife, regardless of who acquired or generated the assets. The transfer of community property without the consent of the partner, particularly without the consent of the wife, becomes a very crucial issue as it can lead to legal and economic losses for the aggrieved party. This research examines the legal protection that can be provided to a wife when community property is transferred without consent and what forms of transfer of community property are carried out without the consent of the wife and what the impacts are. Positive law in Indonesia, through the Marriage Law and the Civil Code, has clearly stipulated that actions regarding community property must obtain the consent of both parties; however, in practice, there are still many violations that harm wives. And forms of transfer of joint property without the wife's consent include sale, donation, collateral, and transfer of ownership to other parties without a valid legal basis. Keywords: Legal Protection, Joint Assets.